Water projects and women's empowerment - Deepa Joshi; Ben Fawcett (2001)
This paper attempts to address this dispute between theorists and practitioners by analyzing each of these four claims of gender successes at the community level, through the perceptions of village women. Do policy and project approaches aimed at enabling increased women’s participation realistically contribute to the empowerment of women in poor and disadvantaged communities?